2018
DOI: 10.1007/s11252-018-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ground surface permeability on the growth of urban linden trees

Abstract: Street trees are an important part of urban vegetation due to their provisioning of different types of ecosystem services such as local climate regulation and contribution to aesthetical and recreational values. In order to provide these services, urban trees need to endure many stress factors not present in natural environments, such as the widespread use of impervious surfaces in the vicinity of street trees. However, few studies have evaluated the effect of this potential stress factor on urban tree growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
2
11
0
4
Order By: Relevance
“…Several field and experimental studies have been conducted on the effects of NaCl on trees, focusing on various issues such as plant tolerance and biochemical and morphological changes, including seedlings and mature trees as well as environmental factors affecting the intensity of salt impact 3 , 4 , 22 24 . Although trees growing in an urban environment are exposed to multiple stresses because of unfavourable microclimate conditions, air pollution, poor surface permeability or mechanical injuries 25 , long-term monitoring studies in the city of Edmonton (Canada) confirmed that both soil salinity and salt spray deposition are among the main abiotic factors contributing to the decline of urban trees 26 . Generally, an excessive accumulation of de-icing salt attributes to poor physiological traits and impoverishment of mycorrhizal symbiosis 27 , which suppress the growth rate and vitality of urban trees.…”
Section: Introductionmentioning
confidence: 99%
“…Several field and experimental studies have been conducted on the effects of NaCl on trees, focusing on various issues such as plant tolerance and biochemical and morphological changes, including seedlings and mature trees as well as environmental factors affecting the intensity of salt impact 3 , 4 , 22 24 . Although trees growing in an urban environment are exposed to multiple stresses because of unfavourable microclimate conditions, air pollution, poor surface permeability or mechanical injuries 25 , long-term monitoring studies in the city of Edmonton (Canada) confirmed that both soil salinity and salt spray deposition are among the main abiotic factors contributing to the decline of urban trees 26 . Generally, an excessive accumulation of de-icing salt attributes to poor physiological traits and impoverishment of mycorrhizal symbiosis 27 , which suppress the growth rate and vitality of urban trees.…”
Section: Introductionmentioning
confidence: 99%
“…L. acuminata tuvo un comportamiento similar al esperado, donde se observó una afectación sobre el crecimiento de la especie en relación con el aumento de las superficies impermeables; con una disminución de AF mientras rasgos como CFMS, DB y DO se vieron incrementados. Yu et al (2018) también reportan afectaciones sobre rasgos foliares de Tilia tomentosa como AFE y CAF (opuesto a CFMS) en relación con el aumento en áreas impermeables, donde las especies buscan generar estructuras más resistentes, dados a los problemas que acarrea la presencia de este tipo de superficies para el desarrollo vegetal como el déficit hídrico, la limitación del crecimiento radicular, reducción de tasas fotosintéticas, el aumento de la temperatura o la disminución de la humedad del suelo, entre otras (Viswanathan et al, 2011;Chen et al, 2017;McClung e Ibáñez, 2018;Sand et al, 2018;Wang et al, 2019, Yan et al, 2019. Las especies Q. humboldtii y S. areira, por otro lado, parecen mejor adaptadas al aumento de las superficies impermeables, donde la primera presentó un aumento en su AF con una disminución en DB, mientras que S. areira tuvo un aumento en los valores de AFE con una disminución en CFMS y la densidad de madera.…”
Section: Discussionunclassified
“…El aumento de este tipo de superficies genera fuertes presiones sobre el desarrollo de los árboles urbanos, pues se evidencian problemas como la disminución en la infiltración de agua, aumento de la compactación, disminución de la porosidad del suelo, del intercambio gaseoso y la disponibilidad de nutrientes, entre otros (Viswanathan et al, 2011;Chen et al, 2017). Todo lo cual puede afectar el desarrollo y esperanza de vida de los individuos arbóreos (Bühler et al, 2007;Just et al, 2018;Sand et al, 2018). Varios estudios han analizado el efecto de la disponibilidad del área de desarrollo, así como de la disponibilidad de agua y condiciones adecuadas del suelo, como consecuencia de la compactación y la impermeabilización del suelo en áreas urbanas alrededor del mundo.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For example, He used association rule analysis to explore the relationship between different urban growth patterns on urban vitality, and the results indicated that different forms of urban growth have different effects on urban vitality [36]. On the other hand, "growth" refers to the growth of urban trees [56,57]. These keywords also include "drought", "tree vitality", "vegetation", and "forest".…”
Section: Abstract Co-occurrence Analysis: Main Topic Distribution Andmentioning
confidence: 99%